KEARIFAN LOKAL: BUDAYA TAHLILAN LINTAS KEYAKINAN DI CIREBON - Sarip Sarip (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2021)
Apart from the pros and cons of tahlilan among Muslims, there are those who do Tahlilan, some are not. For those who do not carry it out in a postulate it is not Islamic teachings originating from the Qur'an and Hadith. Some argue Tahilan is a party that only costs money. The events carried out by various religions and beliefs in the Capar II Block especially the Mosque Block, Urug Block, Sipedang Block, Silawet are a form of religious pluralism. Understanding of Tahlilan in Blok Capar II Hamlet is a real and inseparable part of community life. Integrating tradition or local wisdom values ??with religious values ??is a characteristic of the community of Blok Capar II Hamlet. Tahlilan, which was attended by various religious followers, is a form of religious pluralism that is still difficult to find. Religious pluralism, forming the law of society which later confirmed studies of religious pluralism.